Potential of NK cells in multiple Myeloma therapy. Issue 6 (3rd June 2019) - Khan, Abdullah M.; Devarakonda, Srinivas; Bumma, Naresh; Chaudhry, Maria; Benson, Don M.
ABSTRACT: Introduction : Despite rapid advances in myeloma treatment with the development of new drugs, curative therapies remain elusive. Relapsed/refractory disease related to progressive dysregulation of immune system and acquired genetic abnormalities continues to be a major obstacle in achieving cure. Immune-based therapy harnessing the host defense mechanism of natural killer (NK) cells is a promising avenue in the treatment of myeloma. Areas covered : Here, we discuss the biology and cytotoxic activity of NK cells and the potential role of these innate immune cells in defense against cancer and specifically multiple myeloma. We also discuss the role of NK cells in the anti-myeloma effects of autologous and allogeneic stem cell transplantation, various novel drugs, and treatment modalities such as chimeric antigen receptor therapy. Immune evasion, either directly or indirectly involving NK cell dysfunction, may be a key and under-recognized mechanism in myeloma progression. We reviewed extensive literature identified using the keywords immunotherapy, natural killer cells, and multiple myeloma. Expert opinion : Novel treatment approaches in myeloma utilizing the immunomodulatory and cytotoxic properties of NK cells to eradicate resistant and quiescent clones could pave the way for potentially curative interventions.